Методологічні питання побудови просторових систем підтримки прийняття рішень на основі методів ітеративного агрегування - Suchovirsky, B. I. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
Some methodological aspects of making up spatial systems for supporting decision making for regional management are given. It is shown that processes of iteractive aggregation of the decision for corresponding problems of big dimensionality, which allow to agree the decisions of local problems with the decision of global problems, can serve as the methodological base of such systems.